A Case of Nodular Fasciitis of the Breast Previously Misdiagnosed as Breast Carcinoma; A Case Report - Nazar, Elham; Hashemi, Esmat Alsadat; Ahmadi, Seyed Ali; Baloochi, Keyvan (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: Nodular fasciitis is an exceptional benign soft tissue tumor of the breast that clinically and radiologically can simulate invasive duct carcinoma. Case presentation: We report a case of 67-year-old woman who had a palpable right breast mass of 2 months duration. Sonography showed a hypoechoic heterogeneous round nodule with irregular and speculated borders in right breast. Right breast mass core needle biopsy was inconclusive. Right mastectomy was done due to highly suspicious for malignancy on imaging. Pathological and immunohistochemical examination revealed that the tumor composed of a stellate spindle cell tumor with red blood cells extravasation, compatible with nodular fasciitis. Therefore, pathological evaluation of the lesion is crucial in the assembly of the diagnosis. Conclusion: Nodular fasciitis should be considered in the differential diagnosis of any suspicious breast mass.